Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 1 - Functions - 1.3 Inverse, Exponential, and Logarithmic Functions - 1.3 Exercises: 37

Answer

$f(x)=x^{2}-2x+6$ $f^{-1}(x)=1+\sqrt{x-5}$
1512740178

Work Step by Step

$f(x)=x^{2}-2x+6$, for $x\ge1$ Substitute $f(x)$ by $y$: $y=x^{2}-2x+6$ Solve the equation for $x$. Start by completing the square on the right side. $y=(x^{2}-2x)+6$ Complete the square by adding $\Big(\dfrac{b}{2}\Big)^{2}$ inside the parentheses and subtracting it outside of it. In this case, $b=-2$ $y=\Big[x^{2}-2x+\Big(-\dfrac{2}{2}\Big)^{2}\Big]+6-\Big(-\dfrac{2}{2}\Big)^{2}$ $y=(x^{2}-2x+1)+6-1$ $y=(x^{2}-2x+1)+5$ Factor the expression inside the parentheses, which is a perfect square trinomial: $y=(x-1)^{2}+5$ Take $5$ to the left side: $y-5=(x-1)^{2}$ Take the square root of both sides: $\sqrt{y-5}=\sqrt{(x-1)^{2}}$ $\sqrt{y-5}=x-1$ Take $1$ to the left side and rearrange the equation: $x=1+\sqrt{y-5}$ Interchange $x$ and $y$: $y=1+\sqrt{x-5}$ Substitute $y$ by $f^{-1}(x)$: $f^{-1}(x)=1+\sqrt{x-5}$ The graph of both the original function and its inverse is shown in the answer section.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.